IDENTEFIKASI JENIS MANGROVE DI WILAYAH PESISIR PANTAI TANAH MERAH KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Sepriyani Tessa Boimau; Maya F. Roman; Charisal M. A. Manu; Nur Aini Bunyani (Adisam Publisher, 2025)
Mangrove forests are important mangrove ecosystems with many resources. Physically, mangrove forests are a protective area for land against the effects of wave erosion. Chemically, mangroves act as a source of energy for the availability of waste as a food source for aquatic biota or organisms (Shinta et al 2022). To find out what types of mangroves are in the mangrove forest vegetation in the coastal area of ​​Tanah Merah Beach, Kupang Tengah District, East Nusa Tenggara Regency, to find out the environmental factors that influence the types of mangroves in the mangrove forest vegetation in the coastal area of ​​Tanah Merah Beach, Kupang Tengah District, East Nusa Tenggara Regency. The method used in the study of mangrove type identification is the plot line method referring to the area used as the research location. The results of the study on the identification of mangrove types in the mangrove area show that there are 4 types of mangroves on the Tanah Merah coast, namely Avicennia marina, Sonneratia alba, Rhizopora stylosa, Aegialistis annulata. The most common type found is Avicennia marina and the least is Aegialistis annulata. Based on the identification data of mangrove species in TWAL Teluk Kupang, the most dominant type of mangrove is Avicennia marina.